IPTEK SISTEM INFORMASI AKUNTANSI PADA PENERIMAAN KAS DI PT. SIARAN RADIO MODULASI NADA TITIAN INSPIRASI JAYA MANADO - Tiow, Pattrichsius P; Tirayoh, Victorina Z (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Every organization needs an accounting information system which already planned and supervised well. This article is purpose to know the knowledge and technology (IPTEK) by applying the accounting information system on cash receipts by describing the financial transaction activities occurred. The result of discussion showed that PT Siaran Radio Modulai Nada Titian Inspirasi Jaya Manado already runs their organizational activities well and computerized. It is suggested for the company to maintain their current organizational technology advancement.Keywords: Accounting Information System, Cash Receipt